Electronic structures of Al–Si clusters and the magic number structure Al8Si4. (16th February 2018) - Du, Ning; Su, Mingzhi; Chen, Hongshan
ABSTRACT: The low-energy structures of Al8 Si m ( m = 1–6) have been determined by using the genetic algorithm combined with density functional theory and the Second-order Moller-Plesset perturbation theory (MP2) models. The results show that the close-packed structures are preferable in energy for Al–Si clusters and in most cases there exist a few isomers with close energies. The valence molecular orbitals, the orbital level structures and the electron localisation function (ELF) consistently demonstrate that the electronic structures of Al–Si clusters can be described by the jellium model. Al8 Si4 corresponds to a magic number structure with pronounced stability and large energy gap; the 40 valence electrons form closed 1S 2 1P 6 1D 10 2S 2 1F 14 2P 6 shells. The ELF attractors also suggest weak covalent Si–Si, Si–Al and Al–Al bonding, and doping Si in aluminium clusters promotes the covalent interaction between Al atoms. Abstract :